(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
In this paper, let’s consider constructing an optimal quadrature formula in the mmm-space i.e. in the space of functions whose generalized derivative of order 2 is summed by its Square in the cross section . Furthermore, using Rees’s theorem on the general appearance of a linear continuous functional, finding the error-functional extreme function of a quadrature formula is brought to solve the boundary problem for Ordinary Differential Equations. By solving this boundary problem, a representation of the extreme function of the error functional of the quadrature formula is obtained.